Polyhydroxybutyrate accumulation of \( Bacillus\) sp. strains using water hyacinth hydrolysate as a carbon source - Nguyen, Kim Thoa; Nhung Lai, Thi Hong; Nguyen, Thi Da; La, Thi Huyen; Yen Dao, Hai (Academia Journal of Biology, 2022)
The microbial cells can store energy in the form of polyhydroxyalkanoates (PHAs) while the nutrient sources are exhausted but have an excess of carbon sources. Poly(3-hydroxybutyrate) (PHB) was known as one of the most common PHA. Currently, PHB is assessed as a potential alternative to petroleum-based plastics such as HDPE, PP. In addition, PHB can be obtained from different microbes through the fermentation of renewable and sustainable materials such as waste from food or cassava starch industry, and other agricultural by-products. Although the spread of water hyacinth (Eichhornia crassipes) is becoming a problem in many provinces, it still is considered an opulent biomass source. Besides the application in the removal of heavy metals from wastewater, or making animal feed and fertilizer, water hyacinth can be converted into a carbon source used in microbial fermentation. This paper indicates the PHA synthesis ability of 28 bacterial strains which were isolated from soybean-growing soil samples and the Cau Dien Waste-treatment Plant’s mud samples. Based on their PHA accumulation capability while using C5 and C6 sugars as carbon sources, Bacillus sp. AI 10 and Bacillus sp. CRCXL 2.2 were chosen to synthesize PHA using the water hyacinth hydrolysate as a carbon source. Pretreated water hyacinth biomass using Ca(OH)2 was subjected to enzymatic hydrolysis with a suitable ratio of Cellic→CTec2 and Cellic→HTec2, which resulted in a 409.5 mg total reducing sugars/g pretreated biomass. After 48 hours of fermentation, the dry biomass and accumulated PHA amount from Bacillus sp. AI 10 and Bacillus sp. CRCXL 2.2 were 4.79 g/L, 51.2% and 3.84 g/L, 34.7%, respectively. The Fourier transform infrared spectroscopy (FTIR) spectra of both strains’ PHA structure showed that they can accumulate the homopolymer of PHB. From these results, it is possible to produce PHB by microorganisms from water hyacinth biomass, and participate in the circular bio-economic chain.